Skill based training of accredited social health activists: training effectiveness assessment using training and programme evaluation model - Kant Guleri, Sunil; Gupta, Amarnath; Nandeshwar, Sunil; Dixit, Sanjay; Sakalle, Salil (International Journal of Medical Research and Review, 2017)
Background: Accredited Social Health Activists (ASHAs) are gross root health workers introduced under NRHM; for delivery of health services in rural areas. Training them for capacity building and functioning was a big challenge which has been tackled through skill based training. The study has been done to evaluate training effectiveness using managerial approach (Kirkpatrick’s model) and find out the gaps and suggest measures to improve ASHAs knowledge and skills. Methods: A cross sectional study on 580 ASHAs selected by sequential random sampling at training centres of Indore and Dewas districts. Sample size reduced to 10% of original for qualitative assessment. Interview of subjects and inspection of records was done using questionnaires/Performa. Paired, unpaired t test, Mcnemar test were applied with p<0.05for statistical significance. Results: Significant improvement in knowledge was found and the mean knowledge score got almost doubled after training (from 8.68 to 15.27 in a 30 point score, paired t test p<0.0001). 80% of ASHAs learnt the skills of hand washing, recording temperature and applying eye ointment and 50-60% learnt skill of weighing newborn, preventing baby from cold. Conclusion: Training was helpful in improving knowledge, skills and activities done by ASHAs. But still very few ASHAs were able to score passing marks and competent in all skills essential for new born care.